Analisis Kesesuaian Penggunaan Bahan Ajar Bahasa Mandarin Sekolah Menengah Umum dengan Ketetapan Badan Standar Nasional Pendidikan - Sri Haryanti (Humaniora, 2013)
Teaching material is the important component in teaching and learning process, therefore, choosing the correct one will make easy the achievement of the learning objective.  The Education National Standard Foundation (Badan Standar Nasional Pendidikan) arranges the basic competence standard which will be achieved in learning process as well as the topics which must be covered in the given teaching material. Every education stage has different material, and it is also different for the learner in different study program who will have different teaching material which is in accordance with the field of study and the expected goal. To achieve the good learning objective, the teacher has right to choose the textbook which is going to be used in the learning activities. However, there are also some schools decide to cooperate with other course institutions in running the Mandarin Language teaching and learning activities. The limitation of the availabality of Mandarin textbook which uses Indonesian language gives certain difficulty to the learners not only for the learning activity but also for the process of transferring the knowledge. The writer tries to describe the teaching material used by Senior High School and to see whether that textbook has fulfilled basic competence standard criteria which is going to be achieved by using discussion method with Senior High Schools teachers. It also tries to enlighten the material inside the textbook which is used by the teacher. The writer hopes there will be Mandarin Language Textbook which meets the basic competence standard which is able to support the learners in order to achieve the objective of  the Mandarin Language learning process in Senior High School.